DISPUTE BETWEEN CHINESE AND KOREAN RESEARCHERS CONCERNING TERRITORIAL AFFILIATION OF THE KOGURYO KINGDOM IN THE LIGHT OF ARCHEOLOGICAL EXCAVATION - AŁTYN, Magdalena (International Journal of Korean Humanities and Social Sciences, 2017)
The aim of this article is to summarize knowledge regarding dispute about Koguryo territorial and historical affiliation, which occurred on the political and academic level. Between 37 BC and AD 668 ancient Kingdom of Koguryo embraced large area from central Manchuria to south of Seoul. After year 1945, when Korea regained independence Korean researchers were able to begin their studies on the foundation of the national identity. According to the “Serial Research Project on the History and Current status of the Northeast Border Region” started in China in 2002, Koguryo was an ethnic system in one of the provinces in ancient China. Through this project Chinese historians and archaeologists wanted to incorporate history of Koguryo into the Chinese history, which was not acceptable to Korean researchers. Because of such approach from both sides to this issue, both countries were forced to use archeological excavations and obtained relics in order to show the connection between past and present in both, Koguryo-China and Koguryo- Korea history.